Lamellar versus Micellar Structures—Aggregation Behavior of a Three‐Chain Cationic Lipid Designed for Nonviral Polynucleotide Transfer. Issue 10 (30th June 2015) - Wölk, Christian; Janich, Christopher; Pawlowska, Dorota; Drescher, Simon; Meister, Annette; Hause, Gerd; Dobner, Bodo; Langner, Andreas; Brezesinski, Gerald
Abstract The front cover artwork is provided by the groups of Prof. Bodo Dobner, Prof. Andreas Langner, and research partners Dr. Gerd Hause, Dr. Simon Drescher, and Dr. Annette Meister (MLU Halle‐Wittenberg) as well as the group of Prof. Gerald Brezesinski (MPI of Colloids and Interfaces). The image shows the space‐filling model of a three‐chain amino‐functionalized lipid designed for gene transfer and the preferred pH‐dependent aggregates (multilamellar stacks, vesicles, rod‐like micelles). The background shows a Cryo‐TEM image of rod‐like micelles. Read the full text of the article at 10.1002/cphc.201500188.